EXTH-76. PRMT5 INHIBITION SENSITIZES GLIOBLASTOMA NEUROSPHERES TO TEMOZOLOMIDE. (14th November 2022) - Rivas, Sarah; Rivera-Caraballo, Kimberly; Murphy, Sara; Otani, Yoshihiro; Shelbourn, Allison; Ampie, Leo; Maric, Dragan; Walbridge, Stuart; Shah, Ashish; Yan, Yuanqing; Yoo, Ji young; Heiss, John; et al.
Abstract: INTRODUCTION: The median survival of Glioblastoma (GBM) patients is less than two years with the standard of care of maximal surgical resection, radiation, and temozolomide (TMZ) chemotherapy. Protein Arginine Methyltransferase 5 (PRMT5), which regulates cellular functions by symmetrically di-methylating arginine residues, is overexpressed in GBM. Inhibiting PRMT5 induces apoptosis in differentiated and senescence in stem-like GBM tumor cells. We inhibited PRMT5 in GBM neurospheres to determine if PRMT5 inhibition would enhance TMZ's antitumor effect. METHODS: We depleted PRMT5 activity, in vitro, using target-specific siRNA or LLY-283 and combined these with TMZ treatment. We evaluated the antitumor effect of this combination using cell viability assay, cell cycle analysis, apoptosis assay, and western blot. RESULTS: TMZ reduced the viability of GBMNS with PRMT5 knockdown significantly more than the viability of PRMT5 intact GBMNS. The combination of TMZ and PRMT5 knockdown elevated the expression of cleaved caspase 3 and caspase3/7 indicating that PRMT5 knockdown enhanced the apoptotic effects of TMZ. Cell cycle analysis showed that depleting PRMT5 abrogated TMZ-induced G2/M cell cycle arrest. Further, treatment of PRMT5-depleted GBMNS with TMZ increased ɣ-H2AX expression compared PRMT5 intact GBMNS treated with TMZ, suggesting that PRMT5 depletion enhanced TMZ-induced DNA damage. PRMT5 knockdown also inhibited the symmetric di-methylation of RUVBL1 that is required for homologous recombination repair of TMZ treatment-related DNA damage. CONCLUSION: Overall, PRMT5 inhibition sensitized GBMNS to TMZ and enhanced TMZ-related DNA damage and cytotoxicity. These findings support further development of this potential therapeutic combination.